2012
DOI: 10.1590/s0102-09352012000100001
|View full text |Cite
|
Sign up to set email alerts
|

Immediate physical therapy in dogs with rupture of the cranial cruciate ligament submitted to extracapsular surgical stabilization

Abstract: The study evaluated the influence of immediate physical therapy on the functional recovery of hind limbs of dogs with experimental cranial cruciate ligament rupture which underwent surgical extracapsular stabilization as well as to verify its interference in joint stability. Eight dogs were randomly divided into two groups: GI (control) (n=4) and GII (physical therapy) (n=4). The dogs in GII underwent the following therapeutic treatments in the postoperative period: cryotherapy, passive joint movement, massage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…The strengthening of the periarticular muscles, especially in dogs who are more reluctant to exercise, can also be obtained by neuromuscular electrical stimulation (NMES); this technique is simultaneously effective in reducing edema and pain and in promoting joint mobility [ 183 ]. In a 2008 study, Pellizzari and collaborators demonstrated that NMES can increase the thigh circumference in dogs suffering from atrophy following knee immobilization [ 199 ], confirming the previous results obtained by Johnson and collaborators in 1997 [ 164 , 200 ]. To provide greater stability to the hindlimbs during normal daily activities and to prevent improper movement of the stifle joint, rehabilitation programs also include exercises aimed at strengthening the core muscles.…”
Section: Rehabilitationsupporting
confidence: 66%
See 1 more Smart Citation
“…The strengthening of the periarticular muscles, especially in dogs who are more reluctant to exercise, can also be obtained by neuromuscular electrical stimulation (NMES); this technique is simultaneously effective in reducing edema and pain and in promoting joint mobility [ 183 ]. In a 2008 study, Pellizzari and collaborators demonstrated that NMES can increase the thigh circumference in dogs suffering from atrophy following knee immobilization [ 199 ], confirming the previous results obtained by Johnson and collaborators in 1997 [ 164 , 200 ]. To provide greater stability to the hindlimbs during normal daily activities and to prevent improper movement of the stifle joint, rehabilitation programs also include exercises aimed at strengthening the core muscles.…”
Section: Rehabilitationsupporting
confidence: 66%
“…Rehabilitation can play a pivotal role in restoring the functionality of the injured limb [ 162 , 163 , 164 , 165 , 166 , 167 ]. Regardless of the therapeutic option, the objectives of the rehabilitation protocols are pain management, recovery of normal joint kinematics, periarticular and core muscles strengthening, and correction of proprioceptive deficits [ 156 , 158 , 159 , 162 , 166 , 168 , 169 , 170 , 171 , 172 , 173 ].…”
Section: Rehabilitationmentioning
confidence: 99%
“…Moreover, after the 90 th day post-operative radiographic scores didn't differ significantly from preoperative values which imply that the joints after surgery were stable and no severe osteoarthritis was observed which supports the findings of Jerre (2009). Lameness Score and weight bearing score: The results of lameness and weight bearing are in accordance with Berte et al (2012) who observed improvement in gait in case of physiotherapy group as compared to non physiotherapy group who concluded that the dogs with CCL rupture that undergo immediate physical therapy demonstrate better results in regards to functional gait recovery. Marsolais et al (2002) also observed significant difference in limb function (peak vertical force and vertical impulse) among the physiotherapy group and exercise restricted group.…”
Section: Functional Outcomesupporting
confidence: 72%
“…Thigh girth: The increase in muscle mass had been seen in the physiotherapy group as compared to non physiotherapy group might be due to improved gait and similar findings have been reported by Johnson et al (1997) who suggested that improvement in gait, weight bearing lameness and a decrease in bony changes. Berte et al (2012) all supports that the neuromuscular electrical stimulation and exercise might assist in the prevention of the atrophy by disuse of the operated limb.…”
Section: Functional Outcomementioning
confidence: 68%
See 1 more Smart Citation